COVID-19 and autoimmune diseases: is there a connection?. Issue 2 (11th April 2023) - Votto, Martina; Castagnoli, Riccardo; Marseglia, Gian Luigi; Licari, Amelia; Brambilla, Ilaria
Abstract : Purpose of review: This review summarizes current evidence on the potential link between severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and autoimmunity. Recent findings: Several viral infections are potential triggers of reactive and autoimmune diseases by inducing type II and type IV hypersensitivity reactions. Recent evidence demonstrated that SARS-CoV-2 infection is not an exception, triggering the production of tissue-specific autoantibodies during the acute phase of coronavirus disease 2019 (COVID-19) and leading to autoimmune diseases development as long-term complication. The significant immune dysregulation with cytokine storm and organ damage observed in patients with severe to critical COVID-19 is considered the main mechanism explaining the high levels of autoantibodies, which are also implicated in disease severity and the need for an intensive care assessment. Multisystem inflammatory syndrome in children (MIS-C) is an immune-mediated disease where the recent viral infection leads to systemic inflammation, as already observed in other reactive and autoimmune diseases. Summary: Autoimmunity may be a complication of SAR-CoV-2 infection. Understanding the pathogenesis of autoimmune manifestations in COVID-19 might help prevent the incidence or exacerbation of autoimmune disorders and design better and more efficient treatment strategies in children and adult populations.